A study of chess teacher training practices - Esebua, Meggy (International Scientific Conference “EDUCATION, RESEARCH, PRACTICE” Proceedings, 2024)
Introducing a healthy lifestyle is one of the priorities of the state, which is written in the national goals of general education of Georgia, and at the same time, it is one of the goals of the programs to be implemented by the Minister of Sports and Youth Affairs. They hope to achieve this goal by strengthening the sports sector, and the promotion of chess teaching is also meant among the listed sports. Until 2009, in the Georgian educational space, chess teaching was available only to students of private schools, depending on the market requirements, and the selection of chess teachers was made in accordance with the private requirements of the general educational sector. In the 2022-2024 academic years, the form of learning/teaching chess as a school subject falls within the legal framework, it became a mandatory subject for students of I and II grades, the subject standard of chess appeared, but the document of the teacher's sectoral characteristics, On the basis of which it would be possible to prescribe a chess teacher training program, there is no one available. Given the fact that we do not have school teacher training programs, the chess teachers selected by the school principals do not have the subject Theoretical and practical skills relevant to teaching. The relevance of my topic stems from this problem, that despite the mandatory subject taken into account by the national curriculum, we do not have a document on what field characteristics it should possess. A chess teacher, on the basis of which it would be possible to develop such a training program, after passing which the future school chess teacher will receive the theoretical knowledge, practical skills necessary for teaching the subject and grasp the values ​​that The planning/implementation of students' learning/teaching process should be based on this. Also, despite the fact that chess is a compulsory subject in accordance with the national curriculum, due to the lack of a professional exam for teachers, the school's chess teachers They cannot prove subject competence after which they would be able to join the teacher scheme. Also, due to the lack of a test confirming the subject qualification of a chess teacher, they do not have the opportunity to develop even a chess teacher. The 60-credit teacher training program, which would be a full-fledged tool for the training of those who wish to become a school chess teacher.